Ag nanoparticles decorated PVA-co-PE nanofibrous microfiltration membrane with antifouling surface for efficient sterilization. (October 2020) - Liu, Ying; Cheng, Pan; Guo, Qihao; Liu, Nian; Wan, Yucai; Zhong, Weibing; Lu, Zhentan; Liu, Ke; Sun, Gang; Wang, Dong
Abstract: Microfiltration membrane with antifouling surface for efficient sterilization is of significance to improve the service performance of membrane system in water treatment engineering. Antibacterial property is beneficial for improving the anti-biofouling performance of membrane. Hence, in this work, citrate-capped Ag NPs were decorated on the surface of PVA- co -PE nanofibrous membrane through charge adsorption by the grafted TC-PEI (tricyanogen chloride-polyethyleneimine) on the nanofiber surface. As indicated by the result of morphology and chemical structure analysis, PVA- co -PE nanofibrous membrane with Ag NPs decorated surface has been successfully prepared. The composite membrane presents a stable water permeability with an absolute rejection efficiency of Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) cells. In addition, after attached with the membrane, above bacteria were inactivated effectively with rate of 99.99%. Compared to control samples, the composite membrane presents excellent repetitive-use filtration performance after back-washing test indicating its superior anti-biofouling properties. This can be assigned to the negatively charged surface of citrate-capped Ag NPs, which is beneficial for the penetration of BSA without obvious adhesion behavior to the surface of the membrane. The comprehensive microfiltration performance mentioned above has been attributed to the optimized surface of porous composite membranes synergistically determined by the network nanofiber scaffold and the stably functional surface of citrate-capped Ag NPs, which will bring a new approach in the treatment processing of water body full of microbes. Highlights: PVA- co -PE nanofibrous membrane (NFM) was prepared via nanofiber-suspension-coating. NFM-PEI was prepared through tricyanogen chloride activation and PEI grafting. NFM-AgNPs composite was obtained via adsorbing citrate-capped AgNPs by NFM-PEI. NFM-AgNPs shows excellent sterilization performance with antifouling surface. Properties result from synergistic effect of nanofiber scaffold and anchored AgNPs.